Politics, programs, and budgets : a reader in Government budgeting - Davis, James W. (Englewood Cliffs, N.J. : Prentice-Hall, 1969)
This reader contains recent materials on the growing use of economic analysis in budget making and on the connection between government programs and the government budget.
Bibliographical footnotes.
SJU
Loans
Keywords: Budget; Program budgeting